An adult case of a retroperitoneal isolated enteric duplication cyst with the imaging changes over time - Mayu Inomata; Kengo Kai; Takuto Ikeda; Akiko Ichihara; Rie Masuda; Takumi Kiwaki; Hiroyuki Tanaka; Hiroaki Kataoka; Atsushi Nanashima (Surgical Case Reports)
Abstract Background Adult cases of retroperitoneal isolated enteric duplication cyst (IEDC) are rare, with only 17 case reports in the relevant literature. We herein present a case, which was characterized by changes in intra-cystic density on computed tomography (CT), which was safely resected by laparoscopic surgery. Case presentation The patient was a 60-year-old male who received abdominal CT to investigate the cause of increased serum CA19-9 levels. CT revealed a unilocular cystic mass located in the lower right retroperitoneum. The size increased from 5 to 10 cm in three and a half years and the CT value decreased from 101 Hounsfield Units (HU) to 20 HU. We performed laparoscopic surgical resection, because the possibility that the enlargement of the lesion represented malignant transformation could not be denied. The large cystic mass firmly adhered to the appendix and its mesentery via the retroperitoneum, the appendix was resected en bloc with the cystic lesion. Microscopically, it had no communication with the appendix, and had an intestinal wall structure of muscularis mucosae and muscularis propria. The final pathological diagnosis was IEDC in the retroperitoneal space. There was no histological evidence of malignancy. Conclusion When we encounter a retroperitoneal cystic lesion, we should consider the possibility of malignancy to determine the treatment strategy and perform a careful operation without breaking the cyst wall, irrespective of the preoperative diagnosis.